1996
DOI: 10.1002/pssb.2221960103
|View full text |Cite
|
Sign up to set email alerts
|

Atomic charges in RBa2Cu3O7 superconductor lattices. Electronic structure of the copper atoms

Abstract: The effective atomic charges for all sites of the RBa2Cu 0 7 lattices have been found using our Mossbauer data with the G7C~~("Zn) ,"':j Ba('"'CCs), 'n EufS5Gd) isotopes, our calculations of the lattice electric field gradient (EFG) at the lattice sitcs, as wcll as the I7O NMR data available in literature. The charges show holes placed in the chain oxygen sublattice mainly. The CuZf Sternheimer factor has been estimated and the Cu'+ valence EFG in YBa2Cib07 has been found. The zaxes of the total, lattice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The experimental spectra were resolved into two triplets identified with the 67 Zn 2+ centres at the Cu(1) and Cu(2) sites on the basis of the similarity of the Cu(2) local environments in RBa 2 Cu 4 O 8 and RBa 2 Cu 3 O 7 compound groups. For this reason, we suggested that the asymmetry parameter of the EFG tensor for the Cu(2) sites in RBa 2 Cu 4 O 8 is zero, as it was found to be for RBa 2 Cu 3 O 7 [1]. This requirement was found to be satisfied only for the (2-4-5) triplet ascribed to 67 Zn 2+ centres at Cu(2) sites (figure 1(a)).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The experimental spectra were resolved into two triplets identified with the 67 Zn 2+ centres at the Cu(1) and Cu(2) sites on the basis of the similarity of the Cu(2) local environments in RBa 2 Cu 4 O 8 and RBa 2 Cu 3 O 7 compound groups. For this reason, we suggested that the asymmetry parameter of the EFG tensor for the Cu(2) sites in RBa 2 Cu 4 O 8 is zero, as it was found to be for RBa 2 Cu 3 O 7 [1]. This requirement was found to be satisfied only for the (2-4-5) triplet ascribed to 67 Zn 2+ centres at Cu(2) sites (figure 1(a)).…”
Section: Resultsmentioning
confidence: 94%
“…The valence contribution to the total EFG tensor can be neglected for the 67 Zn 2+ probe [1], and then equation (1) transforms into C(Zn) ≈ eQ(1 − γ )V zz . The lattice EFG tensor was found using the point charge model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations